Analysis of credit department, different activities in risk management division & last four years financial performance (2009-2012) of Bank Asia Limited - Bari, Md. Masudul (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.